True significance of N-acetylglucosaminyltransferases GnT-III, V and α1, 6 fucosyltransferase in epithelial-mesenchymal transition and cancer. (June 2021) - Taniguchi, Naoyuki; Ohkawa, Yuki; Maeda, Kento; Harada, Yoichiro; Nagae, Masamichi; Kizuka, Yasuhiko; Ihara, Hideyuki; Ikeda, Yoshitaka
Abstract: It is well known that numerous cancer-related changes occur in glycans that are attached to glycoproteins, glycolipids and proteoglycans on the cell surface and these changes in structure and the expression of the glycans are largely regulated by glycosyl-transferases, glycosidases, nucleotide sugars and their related genes. Such structural changes in glycans on cell surface proteins may accelerate the progression, invasion and metastasis of cancer cells. Among the over 200 known glycosyltransferases and related genes, β 1, 6 N-acetylglucosaminyltransferase V (GnT-V) (the MGAT5 gene) and α 1, 6 fucosyltransferase (FUT8) (the FUT8 gene) are representative enzymes in this respect because changes in glycans caused by these genes appear to be related to cancer metastasis and invasion in vitro as well as in vivo, and a number of reports on these genes in related to epithelial-mesenchymal transition (EMT) have also appeared. Another enzyme, one of the N-glycan branching enzymes, β1, 4 N-acetylglucosaminyltransferase III (GnT-III) (the MGAT3 gene) has been reported to suppress EMT. However, there are intermediate states between EMT and mesenchymal-epithelial transition (MET) and some of these genes have been implicated in both EMT and MET and are also probably in an intermediate state. Therefore, it would be difficult to clearly define which specific glycosyltransferase is involved in EMT or MET or an intermediate state. The significance of EMT and N-glycan branching glycosyltransferases needs to be reconsidered and the inhibition of their corresponding genes would also be desirable in therapeutics. This review mainly focuses on GnT-III, GnT-V and FUT8, major players as N-glycan branching enzymes in cancer in relation to EMT programs, and also discusses the catalytic mechanisms of GnT-V and FUT8 whose crystal structures have now been obtained. Highlights: GnT-III, GnT-V and FUT8, major players as N-glycan branching enzymes are implicated in various diseases including cancer. These enzymes act as biomarkers for the EMT (epithelial-mesenchymal transition) programs and modify various cell surface proteins. E-cadherin, integrins and related molecules are target proteins of these enzymes and are highly implicated in EMT programs. TGF-b and core EMT transcriptional factors play key roles in the programs.